2013
DOI: 10.4322/polimeros.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Goma de cajueiro (Anacardium occidentale): avaliação das modificações químicas e físicas por extrusão termoplástica

Abstract: Resumo: Países tropicais, como o Brasil, são depositários de uma grande variedade de fontes de polissacarídeos vegetais conhecidos e outros ainda não explorados que possuem grande potencial em aplicações industriais. Alguns estudos reportam a possibilidade de aplicação industrial da goma exsudada do cajueiro em substituição à goma arábica devido à semelhança estrutural e química. Neste estudo propôs-se caracterizar comparativamente algumas propriedades destas duas gomas, antes e após dois tratamentos de extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 6 publications
(6 reference statements)
3
12
0
6
Order By: Relevance
“…Powder X‐Ray Diffraction patterns and the DSC thermograms of the individual polysaccharides, SD, and SD‐loaded matrix beads, presented in Figure A,B, are used to investigate the drug's polymorphism after encapsulation. The P‐XRD patterns of SA and AG polysaccharides are similar to the patterns reported in the literature . The patterns show the presence of semicrystalline regions with 2 broad peaks at 2θ of 13.4° and 22.9° and 12.9° and 22°, for SA and AG, respectively.…”
Section: Resultssupporting
confidence: 82%
“…Powder X‐Ray Diffraction patterns and the DSC thermograms of the individual polysaccharides, SD, and SD‐loaded matrix beads, presented in Figure A,B, are used to investigate the drug's polymorphism after encapsulation. The P‐XRD patterns of SA and AG polysaccharides are similar to the patterns reported in the literature . The patterns show the presence of semicrystalline regions with 2 broad peaks at 2θ of 13.4° and 22.9° and 12.9° and 22°, for SA and AG, respectively.…”
Section: Resultssupporting
confidence: 82%
“…XRD diffractograms for Arabic gum and tannin sources are shown in Figures S2 and S3 (Supplemental Materials). The Arabic gum diffractogram shows two wide bands centered at 18° and 35°, similar to that shown in the literature [24]. Regarding the tannin sources, no differences between the natural galls (nut and oak) were detected, showing two broad bands centered at 15° and 22°.…”
Section: Ingredientssupporting
confidence: 87%
“…All data sets were well fit by the Ostwald de Waale ( R 2 2 > 0.992), with power indices ranging from n = 0.5341 to 1.1330, which demonstrates that carrageenan differed from commercial samples in flow behavior behaviors. Andrade et al () also related the same rheological behavior of extruded arabic and cashew tree gums. It was now demonstrated that the use of extrusion process enhanced the physical properties for the carrageenan gum.…”
Section: Resultsmentioning
confidence: 78%
“…Thermoplastic extrusion was performed in a co-rotating twin screw extruder model Evolum HT25 (Clextral, Firminy, France) equipped with an 8-mm circular die, length:diameter ratio of 40:1 and 10 temperature zones (Vargas-Solórzano, Carvalho, Takeiti, Ascheri, & Queiroz, 2014). Preliminary tests were conduct in order to define process parameters according to Andrade et al (2013). The screw speed and temperature profile were settled according to Table 1 and controlled by Clextral CPU unit.…”
Section: Thermoplastic Extrusionmentioning
confidence: 99%